Structural Characterization of Boro-Titanized AISI 1040 Steel - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
In this study, boro-titanizing treatment was applied to AISI 1040 steel. In the coating treatment, steel samples were pre-boronized in a slurry salt bath consisting of borax, boric acid and ferro-silicon at 900 degrees C for 2 h, then titanized by thermo-reactive deposition technique (TRD) in a powder mixture consisting of ferro-titanium, ammonium chloride, alumina and naphthalene at 1000 degrees C for 1-4 h. The coated samples were characterized by X-ray diffraction analysis (XRD), scanning electron microscope (SEM), glow discharge optical emission spectroscopy (GDOES) and micro-hardness tests. Coated layer formed on the pre-boronized AISI 1040 steel was compact and homogeneous. X-ray studies showed that the phases formed on the steel surfaces are TiB2, TiC, TiN and Fe2B. The depth of the coating layer ranged from 3.41 +/- 0.47 mu m to 6.59 +/- 0.51 mu m, depending on treatment time. A higher treatment time resulted in a thicker boro-titanized layer. The average hardness of the coating layer was 4527 +/- 284 HV0.005.
Keywords: TI-B-C; BEAM-ASSISTED DEPOSITION; NITRIDE COATINGS; FILMS; FABRICATION; RESISTANCE